Calcaneal Stress Reaction with Distal Anchor Fixation for Mid-Substance Achilles Ruptures. Issue 4 (22nd October 2020) - Shoap, Seth C.; Freibott, Christina; Polzer, Hans; Vosseller, J. Turner
Category: Sports; Other Introduction/Purpose: Minimally invasive Achilles rupture treatment has been purported to lead to superior outcomes relative to open treatment. Various forms of minimally invasive treatment exist. One newer technique involves the use of suture proximally that anchors into interference screws distally in the calcaneus. This treatment paradigm potentially addresses some deficiencies of other techniques. However, the authors have noted calcaneal stress reactions in some patients with this technique and here we report our experience. Methods: We conducted a retrospective chart review of patients that had minimally invasive Achilles tendon repair performed by the senior author. Patient demographics, medical history, social history, surgical details, and additional surgeries were recorded. The presence of a calcaneal stress reaction, as evidenced by pain near the calcaneal anchor insertion and confirmed via MRI was reviewed. A comparison was made between those patients that did and did not have a stress reaction. Results: Of the 30 included patients, the average age was 36.93 (+-13.17) and 63.3% were male. The mean BMI in this cohort was 28.76 (+-7.62). 66.7% injured themselves while played a sport. 4 patients (13.3%) had a stress reaction from suture anchors. When comparing those who had a stress reaction to those who did not, independent samples t-test revealed that age (p=0.168) and BMI (p=0.568) were not significantly different between the groups. Chi square noted that gender (p=0.87), ASA score (p=0.449), and mechanism of injury (p=0.486) were not significantly associated. All of the patients that sustained a stress reaction were very fit and active. Conclusion: This case series notes the presence of calcaneal stress reaction in 4/30 patients treated for an Achilles tendon rupture with distal anchor fixation. This stress reaction has not been previously reported. It should be noted that the stress reaction was self-limited in all patients. It typically became symptomatic around the 3-4 month after surgery mark and resolved by 5-6 months.